Sustaining the implementation of alcohol management practices by community sports clubs: a randomised control trial - Tameka McFadyen; Luke Wolfenden; Melanie Kingsland; Jennifer Tindall; Shauna Sherker; Rachael Heaton; Karen Gillham; Tara Clinton-McHarg; Christophe Lecathelinais; Bosco Rowland; John Wiggers (BMC, 2019)
Abstract Background Risky alcohol consumption is responsible for a variety of chronic and acute harms. Individuals involved in organised sport have been identified as one population group who consume risky amounts of alcohol both at the elite and the non-elite level. 'Good Sports', an alcohol management intervention focused on the community sports setting has been successful in addressing risky alcohol use and alcohol-related harm amongst players and sports fans. Sustaining such implementation effects is a common challenge across a variety of community settings. The primary aim of this trial was to assess the effectiveness of a web-based program in sustaining the implementation of best-practice alcohol management practices by community football clubs, relative to usual program care (i.e. control clubs). Methods Non-elite, community football clubs in the Australian states of New South Wales and Victoria, that were participating in an alcohol management program (Good Sports) were recruited for the study. Consenting clubs were randomised into intervention (N = 92) or control (N = 96) groups. A web-based sustainability intervention was delivered to intervention clubs over three consecutive Australian winter sports seasons (April-September 2015-2017). The intervention was designed to support continued (sustained) implementation of alcohol management practices at clubs consistent with the program. Control group clubs received usual support from the national Good Sports Program. Primary outcome data was collected through observational audits of club venues and grounds. Results A total of 92 intervention clubs (574 members) and 96 control clubs (612 members) were included in the final analysis. At follow-up, sustained implementation of alcohol management practices was high in both groups and there was no significant difference between intervention or control clubs at follow-up for both the proportion of clubs implementing 10 or more practices (OR 0.53, 95%CI 0.04-7.2; p = 0.63) or for the mean number of practices being implemented (mean difference 0.10, 95%CI -0.23-0.42; p = 0.55). There were also no significant differences between groups on measures of alcohol consumption by club members. Conclusions The findings suggest that sustained implementation of alcohol management practices was high, and similar, between clubs receiving web-based implementation support or usual program support. Trial registration Australian New Zealand Clinical Trials Registry ACTRN12614000746639. Prospectively registered 14/7/2014.